2009
DOI: 10.1001/archdermatol.2009.49
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Successful Adalimumab Therapy in Severe Hidradenitis Suppurativa

Abstract: Background: Several studies report the use of tumor necrosis factor ␣ (TNF-␣) inhibitors in refractory hidradenitis suppurativa (HS), particularly infliximab and etanercept. However, very limited data have been reported for adalimumab, the newest fully human anti-TNF-␣ monoclonal antibody. We evaluated the long-term efficacy and safety of adalimumab therapy in 6 patients with refractory HS. In the case of positive culture findings from any draining lesion, antibiotic therapy was administered for at least 2 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 25 publications
0
63
1
Order By: Relevance
“…This has to be underlined because infliximab, etanercept and adalimumab appear to be new approaches in severe extensive forms of HS [55,56,57,58]. So, in HS, as Comte et al [59 ]described in psoriasis, we recommend to check for HPV lesions before considering anti-TNF-α treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This has to be underlined because infliximab, etanercept and adalimumab appear to be new approaches in severe extensive forms of HS [55,56,57,58]. So, in HS, as Comte et al [59 ]described in psoriasis, we recommend to check for HPV lesions before considering anti-TNF-α treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, anti-TNF-a biologics are well tolerated, and patients can be treated for prolonged periods [12,64,65].…”
Section: Biologicsmentioning
confidence: 99%
“…It has been suggested that a weekly dose is more effective [3]. In a retrospective study Blanco et al [64] initially started with 40 mg every other week, but in five of the six patients the dose had to be increased to 40 mg every week to prevent relapse. In a large prospective randomized placebo-controlled trial, 40 mg adalimumab weekly was more effective than 40 mg every other week or placebo after 16 weeks of treatment [12].…”
Section: Adalimumabmentioning
confidence: 99%
“…Regarding adalimumab, in both case reports and more extensive studies, an improvement in HS lesions was observed between 4 and 12 weeks of treatment, and the results were maintained for the duration of therapy, despite increasing doses specified in some reports [7,8,9,10,11,12,13,14,15,16,17,18] (data summarized in table 3). Therefore, adalimumab treatment seems to have a favorable outcome in the treatment of HS, with improvement somewhat slower than with infliximab, but maintained over time, with a high safety profile.…”
Section: Review and Discussionmentioning
confidence: 93%
“…Therefore, adalimumab treatment seems to have a favorable outcome in the treatment of HS, with improvement somewhat slower than with infliximab, but maintained over time, with a high safety profile. The main secondary adverse event was edema at the site of injection; other serious adverse effects were exceptional [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. Miller et al [20] conducted a double-blind placebo-controlled study which included 15 patients who received adalimumab 80 mg at week 1 and 40 mg eow for 12 weeks; 6 remaining patients were given a placebo.…”
Section: Review and Discussionmentioning
confidence: 99%